How servant leadership impact the cohesion and burnout of female athlete and how self-identity intermediate the association between servant leadership, cohesion and burnout - Yong Sheng Wang, Hong-Quan Hu , Zhao Chen, Yan Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This paper focuses on the growing importance of servant leadership on the behavior of female athletes. It seems that in the sports sector, servant leadership is not adequately discussed as an important factor in terms of the role of the team captain. Most studies discuss the servant leadership on the upper management point of view, signifying a need to conduct a study on servant leadership in the team captain context because of its potential positive effect on team cohesion, and reduced burnout among female athletes. Serving the followers on a priority basis is the main feature of servant leadership. In the context of sports , servant leadership has been studied and shows positive association with athlete satisfaction, motivation and performance. The aim of the present study is to investigate the association between servant leadership, cohesion and burnout. This study also examine that how self-identity mediates the relationship between servant leadership, cohesion and burnout. Most of the previous studies discuss servant leadership in the setting of upper management, coaches and mentors. However, this study discusses the impact of team captains as servant leader vis-a-vis female athlete cohesion and burnout. To this end, almost 300 questionnaires was distributed, out of which a total of 245 questionnaires are collected from the participants. For data collection, the simple random sampling technique was used. Therefore, in this way it is easier to understand how servant leadership effects the cohesion of female athletes. Servant leadership reduces the levels of anxiety, depression and stress among team members which improves their confidence and enhances their motivation level. The Smart PLS is used for data analysis. The findings of the study elaborated that all hypothesis are accepted, demonstrating a positive influence on cohesion and negative influence on burnout. Furthermore, at the end of study, the practical implications, limitations and future directions for further studies are discussed.